Gender Differences in the Personality Correlates of Reactive and Proactive Aggression in a Spanish Sample of Young Adults - Maneiro, Lorena (Journal of interpersonal violence, 2022)
Since the conceptual distinction of reactive and proactive aggression has been proposed, numerous studies have tried to disentangle the correlates of each function of aggression. While reactive aggression tends to be more strongly related to impulsivity, angry reactivity, or hostility, proactive aggression has proved to be more associated with psychopathic traits and goal-directed behaviors. However, in addition to the current debate about the actual distinction of reactive and proactive aggression, the study of gender differences is still scarce. Thus, the aim of the current study is to evaluate the distinctiveness of reactive and proactive aggression by means of the examination of their differential personality correlates (i.e., HEXACO, psychopathic traits, and impulsivity facets), as well as the assessment of gender differences in those relationships. To that end, a sample composed of 326 young adults aged 18?34 was recruited in Spain. The results evidenced unique associations of reactive and proactive aggression with a set of personality traits, including the HEXACO factors, psychopathic traits, and impulsivity facets, both at raw and residual level. Furthermore, when all the variables were entered in the model, proactive aggression remained strongly related to the factor of Honesty/humility and Emotionality, whereas reactive aggression remained associated with the impulsive/irresponsive factor of psychopathy and, specifically, with the facet of negative urgency, as well as with lack of Agreeableness. Likewise, some gender differences emerged as regards certain correlates. Specifically, proactive aggression was related with lack of Agreeableness and sensation seeking only in males and with the impulsive/irresponsive factor of psychopathy only in females, although these differences were not statistically significant. The conceptual and practical implications of these finding are discussed in terms of prevention.